RELATIONSHIP BETWEEN HUSBAND'S SUPPORT AND EMPLOYEE PARTICIPATION IN VIA EXAMINATION AT RSIA MUHAMMADIYAH PROBOLINGGO CITY - Ririn Ririn; Homsiatur Rohmatin; Agustina Widayati (NHM PRESS, 2023)
One of the policies taken by the government in the prevention and control of cancer, especially cervical cancer, is the Pap smear method or the IVA Test (Visual Inspection with Acetic Acid). Through this activity, it is hoped that public awareness and concern, especially in controlling cancer risk factors and early detection of cancer, is expected to reduce morbidity and mortality from cancer. The purpose of this study was to analyze husband's support with employee participation in IVA examination at RSIA Muhammadiyah Probolinggo City. This study uses a correlational analysis design with a cross sectional approach. The sample data are some of the IVA targets for RSIA Muhammadiyah Probolinggo City employees with simple random sampling technique. Data collection includes, coding, editing, and tabulating which then the data is analyzed by computer with the Spearman test p value: 0.05. The results showed that most of the respondents who had husband's support in the very supportive category were 40 respondents (57.1%) with most of the respondents having high participation to take the IVA examination of 38 respondents (54.3%) and p value: 0.000. The conclusion of the study was that there was husband's support with the participation of female employees in the IVA examination at RSIA Muhammadiyah Probolinggo City (p = 0.000 <0.05). The suggestion put forward is that it is hoped that the hospital can make a policy regarding IVA examinations for employees, especially support from their husbands.